2021
DOI: 10.1039/d1cc01650d
|View full text |Cite
|
Sign up to set email alerts
|

Creating porosity in a trianglimine macrocycle by heterochiral pairing

Abstract: Macrocycles are usually non-porous or barely porous in the solid-state because of their small intrinsic cavity sizes and tendency to close-pack. Here, we use a heterochiral pairing strategy to introduce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Isotrianglimines, although not easy “in collaboration” as calixsalens, are characterized by their not fully explored potential in crystal engineering. The propensity of these compounds to form hybrid materials consisting of molecules differing in their absolute configuration (the heterochiral pairing strategy proposed Cooper) 56 or substitution pattern (formation of cocrystals or solid solutions) is especially interesting. Although the results presented here do not confirm the last hypothesis, the work on this current topic is in progress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isotrianglimines, although not easy “in collaboration” as calixsalens, are characterized by their not fully explored potential in crystal engineering. The propensity of these compounds to form hybrid materials consisting of molecules differing in their absolute configuration (the heterochiral pairing strategy proposed Cooper) 56 or substitution pattern (formation of cocrystals or solid solutions) is especially interesting. Although the results presented here do not confirm the last hypothesis, the work on this current topic is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has Cooper et al reported crystal structures of optically pure and racemic 3a . 56 In the crystal, the optically pure 3a molecules form pillars containing solvent molecules in their cavities. A heterochiral pairing strategy introduced porosity when ( rac )- 3a was crystallized and packed in the lattice using head-to-head supramolecular motifs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallization of chiral tiranglimine macrocycle using a heterochiral paring strategy may introduce porosity into the crystal framework. This was observed in the macrocyclic polyiminines that do not exhibit high porosity in the enantiopure form [ 64 ]. Cooper at al proved this using the example of a simple triangilimine derived from condensation of trans -1,2-diaminocyclohexane and isophthalic aldehyde.…”
Section: Nitrogen-containing Macrocycles—applicationsmentioning
confidence: 98%
“…Hence, Cooper et al . recently revisited the iso ‐TA based macrocycle T1 regarding the porosity of the system, speculating that the adsorption kinetics can be enhanced [26b] . Gas adsorption experiments with R ‐ T1 showed that activation of the crystalline sample resulted in a basically non‐porous polycrystalline material ( SA BET ≈4 m 2 g −1 ), due to collapsing of the pores upon solvent removal.…”
Section: Triangliminesmentioning
confidence: 99%